High accuracy walking motion trajectory generation profile based on 6-5-6-PSPB polynomial segment with polynomial blend - Mohammed, Marwan Qaid Abdulrazzaq (UTeM, 2018)
Many robots, such as humanoid robot, biped robot, and robotic exoskeleton, need human guide. Particularly, there is a strong need for devices to assist individuals who lost limb function due to illnesses or injuries. Thus, several methods of generating walking motion have been implemented in order to generate walking motion according to natural human behaviour for the exoskeleton robot system. Polynomial blend technique has implemented to generate the walking motion trajectory, where the polynomial blend refers to the combination of more than one polynomial. However, three constraints (angular position, velocity, and acceleration) have been imposed by the polynomial blend techniques where the constraint of angular jerk was neglected because involving the jerk constrain will be caused problem of the non-ideal match of kinematic constraints at via point. Based on the aforementioned problem, there are three objectives to be achieved in this project. The first objective is to investigate the trajectory profile for various kinematic constraints of walking motion condition when using polynomial equation. The second objective is to modify a technique for improving a trajectory generation method to solve the problem of non-ideal match of the kinematic constraints through via points that connects between successive segments of the human walking motion. The last objective is to validate the trajectory generation method by testing the trajectory generation methods based on simulation using SimMechanics as well as to ensure that the coefficients values of the polynomial equations are correctly obtained. In this project, 5th polynomial segment with the 6th polynomial blend (6-5-6 PSPB) trajectory is proposed that aims to reduce the error that increases because of non-ideal match between kinematic constraints at the via points of successive segments. The trajectory planning of the 6-5-6 PSPB is generated based on the stance and swing phases. Each phase is presented by one full of the 6-5-6 PSPB trajectory. In order to validate the 6-5-6 PSPB trajectory, simulation using SimMechanics is conducted to ensure that the coefficients values of the polynomial equations are correctly obtained. The result shows that the error was improved almost 0.1445 degree based on the proposed 6-5-6 PSPB compared with the 4-3-4 PSPB and 5-4-5 PSPB. Thus, the 6th -5th -6th Polynomial blend leads to impose the angular jerk kinematic constraint beside the angular position, velocity, and acceleration kinematic constraints during the whole walking motion trajectory. Minimizing the maximum jerk in joint space has a beneficial effect in terms of reducing the actuator and mechanical strain and joint wear and to limit excessive wear on the robot and the excitation of resonances so that the robot life-span is expanded.